Punk rock, so what? : the cultural legacy of punk - Sabin, Roger, 1961- (Routledge, 1999)
Punk Rock: So What? brings together a new generation of writers, journalists and scholars to provide the first comprehensive assessment of punk and its place in popular music history, culture and myth.
Keywords: Punk rock music -- History and criticism.; Alternative rock music -- History and criticism.; Punk (Musique) -- Histoire et critique.; Rock alternatif -- Histoire et critique.; MUSIC -- Genres & Styles -- Punk.; MUSIC -- Genres & Styles -- Heavy Metal.; MUSIC -- Genres & Styles -- Rock.; Alternative rock music; Punk rock music; Electronic books.; Criticism, interpretation, etc.